ADDED VALUE SAMPAH ORGANIK DENGAN TEKNOLOGI KOMPOSTER UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT GAYO JEMBER-BONDOWOSO - Amri Gunasti; Abadi Sanosra (JPM PAMBUDI, 2020)
Waste generation in Jember and Bondowoso districts is estimated at more than 500 m3day. More than 70% is organic waste. It can have multiple effects. There are three main products produced from this program, the first is composter, the second is HCS bioactivator and the third is liquid compost. The approach method includes stages: a). Socialization of PKMS program on Composter and Compost Making Technology b). Preparation of social preconditions, i.e. Coordination with the Gayo Jember Community regarding solving problems faced by members c). Implementation of the Composter Making technology and compost technology application programs, both technical and non-technical for the community, d). Monitoring, evaluation and reporting. The implementation of the Community Stimulation Partnership Program (PKMS) Composter Technology and Household Scale composting will improve the optimization of household waste function as raw material for organic fertilizer, increasing the income and welfare of members of the Gayo Jember-Bondowoso Community.